2000
DOI: 10.1007/s002040050004
|View full text |Cite
|
Sign up to set email alerts
|

NAD(P)H quinone oxidoreductase 1 codon 609 polymorphism and its association to colorectal cancer

Abstract: The present study used a rapid and single-step method for genotyping of NAD(P)H quinone oxidoreductase (NQO1) codon 609 polymorphism using real-time polymerase chain reaction (PCR)-analysis and subsequent melting curve analysis for the analysis of allelic distribution of NQO1. The design was a case control study of 323 Caucasians with colorectal cancer and 205 healthy controls. There was no difference in the frequencies of the mutated NQO1 allele (NQO1*2): 0.190 for control individuals and 0.195 for cancer pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 5 publications
3
17
1
1
Order By: Relevance
“…The ORs for the NQO1 *2/*2 genotype in these studies, which totaled 1,343 patients with colorectal cancer and 1,440 control subjects, ranged from 1.5 to 2.9. However, the current results differ from three other studies with colon cancer patients, which found no significant difference in the NQO1 genotype distribution in the patient population compared with controls (42,54,55). These latter studies totaled 887 patients with colorectal cancer and 1,438 controls.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The ORs for the NQO1 *2/*2 genotype in these studies, which totaled 1,343 patients with colorectal cancer and 1,440 control subjects, ranged from 1.5 to 2.9. However, the current results differ from three other studies with colon cancer patients, which found no significant difference in the NQO1 genotype distribution in the patient population compared with controls (42,54,55). These latter studies totaled 887 patients with colorectal cancer and 1,438 controls.…”
Section: Discussioncontrasting
confidence: 99%
“…However, three other studies showed no significant differences in NQO1 genotype frequencies between patients with colorectal cancer and healthy controls (42,54,55). A recent meta-analysis suggested a statistically significant association of the NQO1 *2 allele with a moderately elevated risk of developing colorectal cancer (56).…”
Section: Introductionmentioning
confidence: 97%
“…13 CYP2E1*5B as described by Choi et al, 14 and NQO1*2 as described by Harth et al 15 For the detection of MTHFR C677T we followed the method recommended by Roche (Applied Science), using the primers MTHFR_s (cgaagcagggagctttgaggctg) and MTHFR_as (aggacggtgcggtgagagtg) and the hybridization probes MTHFR_LC labeled with Red640 at the 5é nd (LC Red640-cgggagccgatttcatcat-ph) and MTHFR_3FL (tgacctgaagcacttgaaggagaaggtgtc X) labeled with fluorescein. The del{GSTT1} and del{GSTM1} polymorphisms were detected following the conventional PCR method of Naoe et al, 16 comprising a multiplex PCR that co-amplifies the target genes simultaneously with the β-globin gene used as a reference control gene.…”
Section: Genotyping Of Polymorphismsmentioning
confidence: 99%
“…6 NQO1 gene located on chromosome 16 (16q22.1) encodes an obligate two-electron reductase that can either bioactivate or detoxify quinones and has been proposed to play an important role in chemoprevention. 7 The polymorphism in exon 6 of NQO1 (C609T, Pro187Ser, NQO1*1/ *2) was associated with the risk of colorectal cancer 8 and myeloid leukemia. 9 The case -control study of Hamajima et al 10 on Japanese suggested that the variant NQO1*2/*2 genotype increased the risk of cancers of the esophagus and lung but not breast.…”
Section: Introductionmentioning
confidence: 99%